2009
DOI: 10.1080/87565640903325733
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Non-Spatial Working Memory Capacity During Childhood and Adolescence and the Role of Interference Control: An N-Back Task Study

Abstract: To investigate the role of interference control on the development of working memory (WM) capacity, 6-12-year-old children and adults performed an N-Back task with differing WM-load and interference control demands. Correlation analyses between flanker interference scores and WM-load levels showed that interference control was only required in the 2-back condition. While WM maintenance (1-back task) reached adult accuracy levels at age 10-12, the ability to maintain information in WM during distraction (2-back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 61 publications
7
41
0
Order By: Relevance
“…We thus observed a relatively protracted development of resistance to interference, which is consistent with new evidence on developmental trajectories in the n -back (Schleepen & Jonkman, 2010). Our model shows this protracted development due to an interdependency between the resolution of proactive interference and other executive functions: Gating, maintenance, and binding control processes, supported by reinforcement learning (in the case of gating) as well as Hebbian and error-driven learning, must first construct a relatively stable state before those representations can be incrementally refined to reduce proactive interference through additional Hebbian and error-driven learning.…”
Section: Resultssupporting
confidence: 89%
“…We thus observed a relatively protracted development of resistance to interference, which is consistent with new evidence on developmental trajectories in the n -back (Schleepen & Jonkman, 2010). Our model shows this protracted development due to an interdependency between the resolution of proactive interference and other executive functions: Gating, maintenance, and binding control processes, supported by reinforcement learning (in the case of gating) as well as Hebbian and error-driven learning, must first construct a relatively stable state before those representations can be incrementally refined to reduce proactive interference through additional Hebbian and error-driven learning.…”
Section: Resultssupporting
confidence: 89%
“…Several behavioral studies have shown that adolescents have still immature WM performance, mainly in tasks requiring high levels of executive control [19], [20], [21]. This raises the question of whether this worse performance than adults is caused by still immature WM processing capacity during the encoding of items for maintenance in WM or whether other processes like memory comparison or response decision times also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, one such important executive process is filtering efficiency, that is, the efficiency with which the individual is capable of excluding irrelevant information to get access to, or interfere with the current contents of WM. Schleepen and Jonkman [21] showed particularly late development of non-spatial WM-capacity into adolescence in task conditions requiring simultaneous maintenance, updating and suppression of irrelevant information.…”
Section: Introductionmentioning
confidence: 99%
“…The present study focuses on adolescence since both WM-capacity and inhibitory control have been consistently reported to follow a protracted qualitative development into this period, especially in situations that are highly cognitively demanding (Anderson et al, 2001;Davies and Rose, 1999;Demetriou et al, 2002;Gathercole, 1999;Klingberg et al, 2002;Kwon et al, 2002;Leon-Carrion et al, 2004;Luciana et al, 2005;Luna et al, 2004Luna et al, , 2010Schleepen and Jonkman, 2010;Segalowitz et al, 2010). For example in a review article, Gathercole (1999) showed that especially complex working memory (compared to phonological and visuospatial short-term memory) undergoes late development until 16 years of age.…”
Section: Introductionmentioning
confidence: 94%
“…Luciana et al (2005), who used nonverbal WM tasks with varying degrees of executive demands, reported that WM-capacity in a spatial WM task in which sequences of visually presented information (block tapping) had to be recalled in backward order (requiring maintenance and manipulation) did not reach mature levels in adolescents until 13 or 15 years of age. Schleepen and Jonkman (2010) showed particularly late development of non-spatial WM-capacity into adolescence in task conditions that required simultaneous maintenance, updating and suppression of irrelevant information in a verbal N-back task. Luna et al (2004) also showed ongoing development of working memory throughout adolescence using an oculomotor delayed response task (requiring eye movements guided by a target location in memory), as well as late development in adolescence of inhibitory control in an anti-saccade task.…”
Section: Introductionmentioning
confidence: 98%